Mergers and Acquisitions: Lessons Learned from Indonesia's State-Owned Enterprises - Sudaryono; Hakim , Dedi Budiman; Manurung, Adler Haymans; Asikin, Zenal (Universitas Pendidikan Ganesha, 2025)
This study examines the impact of mergers and acquisitions on the financial performance of Indonesia’s state-owned enterprises, specifically in terms of Return on Assets (ROA), Return on Equity (ROE), and the Price-to-Earnings (P/E) Ratio. To test the hypothesis, the research incorporates fundamental factors such as Revenue, Current Ratio, and Debt-to-Equity Ratio, alongside external influences like Exchange Rate, Oil Price, and the COVID-19 pandemic. Mergers and acquisitions are considered moderating factors in this relationship. This study employs a Panel Data Regression Model using Generalized Least Squares (GLS) for initial estimates, followed by Ordinary Least Squares (OLS) to further refine the analysis. The data is sourced from 132 publicly listed Indonesia's state-owned enterprises on the Indonesia Stock Exchange, covering the period from 2010 to 2021. The study shows that Revenue significantly affects ROA, ROE, and P/E Ratio, while the Debt-to-Equity Ratio impacts ROA and P/E Ratio. Among external factors, the exchange rate influences both ROA and ROE. The analysis reveals that mergers and acquisitions lead to notable changes in financial performance, particularly in the P/E Ratio, where Revenue and Debt-to-Equity Ratio have a stronger effect. Additionally, when combined with the Current Ratio, mergers and acquisitions enhance their impact on ROA, ROE, and P/E Ratio. These findings suggest that holding policies improve operational efficiency in Indonesia’s state-owned enterprises and that investors benefit from potential capital gains following merger announcements. However, while the holding policy shows positive results, further governance improvements are needed for long-term success.